Micro- and Nano-Carrier Mediated Intra-Articular Drug Delivery Systems for the Treatment of Osteoarthritis - Zhiyue Zhang; Guihua Huang (Journal of Nanotechnology)
The objective of this paper is to provide readers with current developments of intra-articular drug delivery systems. In recent years, although the search for a clinically successful ideal carrier is ongoing, sustained-release systems, such as polymeric micro- and nanoparticles, liposomes, and hydrogels, are being extensively studied for intra-articular drug delivery purposes. The advantages associated with long-acting preparations include a longer effect of the drug in the action site and a reduced risk of infection due to numerous injections consequently. This paper discusses the recent developments in the field of intra-articular sustained-release delivery systems for the treatment of osteoarthritis.